The interaction of maleic anhydride and derivatives of long-chain olefins - Ал-Хаддад, Джасим Амир Т.; Киселёва-Логинова, Екатерина Валерьевна; Попов, Евгений Вадимович (Eastern-European Journal of Enterprise Technologies, 2014)
The possibility of interaction between maleic anhydride and derivatives of long-chain olefins, where the double bond is in the depth of the hydrocarbon chain was considered in the paper. Available and cheap natural raw material - oleic acid is taken as such olefin. It was assumed that the nucleophilic addition of oleic acid to maleic anhydride by the double bond with retaining the molecular structures may proceed by the Alder mechanism under appropriate conditions: reaction temperature of more than 150ºC or in the presence of Lewis acid-type catalysts. Series of syntheses in melts and organic solvents: trihloretilene, perhloretilene and o-xylene were conducted. Reaction temperature modes were from 130ºC (boiling temperature of solvents) to 210ºC. As a result, three types of products were obtained: white crystal sediment, colorless plates and viscous filtrate from light brown to dark brown. The products were separated by different solvents, identified by the melting point and the acid number. The target reaction products were colorless plate crystals with the acid number of 369.6 mg KOH/g and the melting point of 140-142ºC. Additional analyses (IR and NMR spectroscopy) have shown that the plates are the product of addition of oleic acid residue to maleic anhydride by the double bond. The resulting substance possesses surfactant properties. Thus, during studies, it was proved that the addition of olefins with the double bond in the center of a hydrocarbon radical with structure retaining to maleic anhydride is impossible in conditions, specified in the literature.